Starlink Network Technology Analysis Using Quality of Service Analysis Method (Case Study: Karya Jaya Village, Kertapati) - Muhammad Wahyu Distira; Karnadi; Apriansyah (Universitas Islam Kuantan Singingi, 2025)
This study focuses on analyzing the quality of service (QoS) and measuring the quality of the internet network on the Starlink network In Karya Jaya Village, this study uses the QoS parameter measurement method. The parameters used include delay, jitter, packet loss, and throughput. This measurement is done using the Wireshark application to monitor and capture the traffic of data packets in the network. This application provides detailed information about network performance and can identify potential problems in the data transmission process. The throughput measurement results showed that the throughput was higher during sunny weather, with a value of 74k, compared to the rainy weather time which only reached 158k. Despite the difference in throughput values, the two values still showed